Shall We Dance - Chelsom, Peter; Anita, Gillette; Bobby Cannavale; Jennifer Lopez; Lisa Ann Walter; Stanley Tucci; Susan Sarandon; Richard Gere (USA Miramax, 2004)
John Clark is a man with a wonderful job, a charming wife and a loving family, who nevertheless feels that something is missing as he makes his way every day through the city. Each evening on his commute home, John sees a beautiful woman, staring with a lost expression through the window of a dance studio. Haunted by her gaze, John impulsively jumps off the train one night, and signs up for dance lessons, hoping to meet her. At first, it seems like a mistake. His teacher turns out to be not Paulina, but the older Miss Mitzi, and John proves just as clumsy as his equally clueless classmates on the dance-floor. Even worse, when he does meet Paulina, she icily tells John she hopes he has come to the studio to seriously study dance and not to look for a date. But, as his lessons continue, John falls in love with dancing. Keeping his new obsession from his family and co-workers, John feverishly trains for Chicago's biggest dance competition. His friendship with Paulina blossoms, as his enthusiasm rekindles her own lost passion for dance. But the more time John spends away from home, the more his wife becomes suspicious. With his secret about to be revealed, John will have to do some fancy footwork to keep his dream going and realize what it is he really yearns for.
A romantic comedy where a bored, overworked Estate Lawyer, upon first sight of a beautiful instructor, signs up for ballroom dancing lessons.
Masayuki Suo
Languages : English, Turkish
Subtitles : English, Turkish
Keywords: Comedy; Music; Romance; Drama